THERMAL PERFORMANCE OF THERMOSYPHON FOR DIFFERENT WORKING FLUIDS - Russo, G. M.; Krambeck, L.; Nishida, F. B.; Santos, P. H. D.; Alves, T. Antonini (Revista de Engenharia Térmica, 2016)
In this paper, an experimental investigation was performed of the thermal performance of different working fluids in thermosyphons that can be used in thermal control of electronic equipment. The working fluids were considered acetone, water, ethanol, and methanol. The thermosyphon are manufactured of copper with an outer diameter of 9.45 mm, an inner diameter of 7.75 mm, a total length of 200 mm, whereas an evaporator of 80 mm length, an adiabatic region of 20 mm in length and a condenser of 100 mm in length. They were loaded with 1.39 ml of the working fluid, corresponding to a filling ratio of 40% of the evaporator volume. Experimental tests were performed in a vertical position considering thermal loads between 5W and 25W. The thermosyphons operated satisfactorily in all the tests. The operating temperature distribution as a function of time and the heat resistance behavior as a function of power dissipation have been presented for each analyzed working fluid. These results indicated that acetone is the working fluid that has the best thermal performance.